1980
DOI: 10.1063/1.440620
|View full text |Cite
|
Sign up to set email alerts
|

Ion fragmentation from noninterconverting electronic states

Abstract: The photoionization and fragmentation of CH3ONO+ were studied using threshold photoelectron-coincident photoion mass spectrometry, photoelectron spectroscopy, and triple sector mass spectrometry.(AIP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The results of our mass spectral measurements and calculations both explain the findings of previous mass spectrometry studies on NM radical cation and identify new dissociation pathways from higher cation charge states of NM. The contribution of both singly and multiply charged cations to shock detonation in energetic materials , makes the decomposition pathways, identified in this work, of potential importance to the energetic performance of NM.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The results of our mass spectral measurements and calculations both explain the findings of previous mass spectrometry studies on NM radical cation and identify new dissociation pathways from higher cation charge states of NM. The contribution of both singly and multiply charged cations to shock detonation in energetic materials , makes the decomposition pathways, identified in this work, of potential importance to the energetic performance of NM.…”
Section: Discussionsupporting
confidence: 84%
“…The dissociation reactions of isolated NM radical cation have been studied for decades with mass spectrometry. Since the 1980s, the NM radical cation has been known to exist in three isomeric forms shown in Scheme , with both the methylnitrite and aci -nitromethane structures accessible from the ionized parent nitromethane structure . Both the methylnitrite and aci -nitromethane cation states are lower in energy than the parent NM cation state. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qian et al [34,41] recently reviewed the available information about the unimolecular dissociation and CAD of the acetone, methyl nitrite, and nitromethane cations. They indicated that several of these studies had concluded that the dissociation of the nitromethane [42,43] and methyl nitrite [43,44] cations (to NO+, MeO+, and Me+) and acetone cation (to MeCO+ [17,23,25,27,[30][31][32][33][34] and Me+ (29]) cannot be described by QET. J Am Sue Mass Spectrum 1992,3,427-444…”
Section: Discussionmentioning
confidence: 99%
“…Molecular beam studies of the CAD of the nitromethane cation [41] (which also has electronically isolated states [40]) have indicated that its low energy CAD also involves electronic transitions (rather than vibrational excitation) [41]. Other examples of non-QET behavior have been reported previously [42][43][44].…”
Section: Energy Transfer Efficiency4mentioning
confidence: 99%